SUITABILITY OF CLUSTERBEAN VARIETIES FOR RAINFED ALFISOLS OF SCARCE RAINFALL ZONE - C. RADHA KUMARI (The Journal of Research ANGRAU, 2016)
A field experiment was conducted to study the suitability of clusterbean varieties for alfisols of scarce rainfall zone under rainfed conditions for two years during kharif, 2014-15 and 2015-16 at Agricultural Research Station, Anantapur, Andhra Pradesh. Results revealed that number of pods plant-1, test weight, seed yield and haulm yield was not significantly influenced by different varieties during both the years of experimentation. The correlation studies between yield attributes and yield based on two years investigation revealed that number of seed per plant was significantly and positively influenced by plant height and number of pods plant-1. The test weight has significant positive correlation with plant height, number of pods and number of seeds plant-1. Seed yield was positively and significantly correlated with number of pods plant-1, number of seeds plant-1 and test weight. The haulm yield expressed significant positive correlation with number of seeds plant-1 and seed yield. Performance of all clusterbean varieties was similar under rainfed conditions of scarce rainfall zone and farmers can grow any of the varieties tested for profitable yield.